Morphological analysis of the alimentary canal of Plutella xylostella (Linnaeus, 1758) (Lepidoptera: Plutellidae) submitted to microencapsulated formulation of Annona muricata L. (Annonaceae) - Leonara Evangelista de Figueiroa; Priscylla Costa Dantas; Ellen Carine Neves Valente; Alice Maria Nascimento Araújo; José Pedro da Silva; Roseane Cristina Predes Trindade (Ciência Rural)
ABSTRACT: This study obtained information about the external and internal morphology of the alimentary canal of the main pest of brassica, Plutella xylostella L. (Lepidoptera: Plutellidae), when it is exposed to a microencapsulated formulation of the seed extract of Annona muricata L. (Annonaceae). The toxicity of the microencapsulated formulation of the caterpillars fed for 12, 24, and 48 hours plus the control was evaluated to verify and evaluate external and internal morphological changes caused by the extract that may have killed the caterpillars. After the assays, the alimentary canal of the caterpillars was dissected, fixed, dehydrated, blocked, cut, and colored. Then, histological slides were produced and studied under light microscopy and scanning microscopy (SEM). The microencapsulated formulation of A. muricata caused irreversible damage to the alimentary canal of P. xylostella, with disorganization, cell stratification, and modifications in the morphology of the cells considered essential for survival. SEM verified that the peritrophic membrane and the muscular layer remained intact during all the assays. The effects were more severe with more hours of exposure. These results demonstrated that after contact by ingestion, the insect dies due to intoxication and cellular disorganization, inhibiting its ability to continue feeding.